BAGAIMANA TATA KELOLA PERUSAHAAN DAN NEGARA BERINTERAKSI DALAM PENGUNGKAPAN LINGKUNGAN PERUSAHAAN DI ASEAN? - Athfalina, Vidya Intani; Hermawan, Ancella Anitawati (Universitas Multimedia Nusantara, 2023)
Abstract” This study tries to determine how the regulatory environment of the nation interacts with company governance to affect the amount of pengungkapan lingkungan. The research uses quantitative methods (panel data regression). Data was obtained from a database of 109 ASEAN public companies during 2012-2020. The results demonstrate that: (1) Higher environmental disclosures is more likely to occur in firms with great corporate governance (β = 0,002; p-value<0,05). (2) Likewise, if the company operates in a country with supportive state governance (β = 0,008; p-value<0,1). (3) Corporate and state governance work together (complementary) regarding environmental disclosures (β = 0,000; p-value<0,1). The research contributes evidence on the association connecting corporate governance and agency theory and supports it, the state and environmental disclosures. The study emphasizes the significance of environmental disclosures in combating climate change as well as ASEAN's low level of awareness and compliance. The study findings provide further insight by interacting corporate and state governance which are the two main considerations for environmental disclosure. Keywords:ASEAN; Agency Theory; Corporate Governance; Country Governance; Environmental Disclosures.